BUGIS LANGUAGE MAINTENANCE STRATEGY IN LOMBOK - Azis, Atri Dewi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
Bugis language is one of the Bugis ethnic cultural identities, which is still considered safe because it has a very large number of speakers throughout Indonesia. However, this language may undergo an extinction process, if there are no strategic efforts to maintain it. Therefore, the purpose of this study is to reveal the strategy of retaining Bugis speakers in Lombok to preserve the local language. The research was conducted at Paremas East Lombok in June-August 2019. This research used a descriptive quantitative approach. The results showed that the number of Bugis speakers in Lombok still exists, but the number is very small. Strategy to maintain the Bugis language in Lombok can be carried out in several steps, namely, encouraging Bugis people to continue to use the Bugis language in everyday life, promoting the use of Bugis language in the mass media, providing opportunities for Bugis ethnic students to learn their local language at school, and enlivening traditional art activities by telling stories using the Bugis Language. Keywords: local language, Bugis, ethnic, speakers